2008
DOI: 10.3181/0712-rm-337
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress and NFkB in Hypoxia-Induced Pulmonary Edema

Abstract: Hypoxia is well known to increase the free radical generation in the body, leading to oxidative stress. In the present study, we have determined whether the increased oxidative stress further upregulates the nuclear transcription factor (NFkB) in the development of pulmonary edema. The rats were exposed to hypobaric hypoxia at 7620 m (280 mm Hg) for different durations, that is, 3 hrs, 6 hrs, 12 hrs, and 24 hrs at 25+/-1 degrees C. The results revealed that exposure of animals to hypobaric hypoxia led to a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 45 publications
3
86
1
5
Order By: Relevance
“…Overexpression of miR-27b* mimics might negatively regulate its target proteins, which may be critical for NF-kB activation and the absence of these proteins in cells transfected with miR-27b* mimics might have led to either failure of NFkB activation or active suppression of NF-kB. To verify whether overexpression of miR-27b* can alter NF-kB-dependent gene expression, we measured mRNA expression for IL-1β, IL-6, TNF-α, and Ccl2 by TaqMan PCR analysis [40][41][42][43]. While there were no differences in the expression of IL-1β, IL-6, and TNF-α, Ccl2 mRNA expression was lower in the cells transfected with miR27b* mimics as compared with that of control mimics ( Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of miR-27b* mimics might negatively regulate its target proteins, which may be critical for NF-kB activation and the absence of these proteins in cells transfected with miR-27b* mimics might have led to either failure of NFkB activation or active suppression of NF-kB. To verify whether overexpression of miR-27b* can alter NF-kB-dependent gene expression, we measured mRNA expression for IL-1β, IL-6, TNF-α, and Ccl2 by TaqMan PCR analysis [40][41][42][43]. While there were no differences in the expression of IL-1β, IL-6, and TNF-α, Ccl2 mRNA expression was lower in the cells transfected with miR27b* mimics as compared with that of control mimics ( Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, when an oxygen shortage first occurs, ROS originating in the mitochondria lead to reduced Na + -K + -ATPase activity in alveolar epithelial cells, a phenomenon also observed in HAPE (Dada et al, 2003). Finally, it has been shown that high altitudeinduced ROS and the overwhelmingly high oxidative stress that results may up-regulate nuclear factor kappa B and cause increased transvascular leakage in the lungs of mice (Sarada et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…The combined observation and detection of SOD, MDA, and IL-6 in the lung tissue of patients with acute pulmonary edema can comprehensively reflect alterations in the physiological state of patients, and is conducive to the effective diagnosis, treatment and prognosis of patients with acute pulmonary edema (22). In the present study, changes in the levels of MDA and SOD in the lung tissue of a rat model of hypoxia-induced acute pulmonary edema were compared at various durations of acute hypoxia and against the group A control.…”
Section: A B C D Discussionmentioning
confidence: 99%